HIV and gender identity expression among transfeminine people in the Western Cape, South Africa - a thematic analysis of data from the HPTN 071 (PopART) trial - Laing de Villiers; Leslie Swartz; Peter Bock; Janet Seeley; Anne L. Stangl; Virginia Bond; James Hargreaves; Graeme Hoddinott (BMC, 2024)
Abstract Introduction Transfeminine people in South Africa have a high HIV risk due to structural, behavioural, and psychosocial factors. Transfeminine people and feminine identifying men who have sex with men (MSM) are often conflated or grouped with transgender or MSM categories in HIV service programming, although they don't necessarily identify as either. We aimed to investigate gender expression among feminine identifying people who were assigned male at birth. We examined how local conceptualizations of sexuality and gender intersect with the key population label of 'transgender' imported into local HIV programming. Methods A qualitative cohort nested within the HPTN 071 (PopART) trial included longitudinal, in-depth interviews with eight transfeminine people (four who disclosed as living with HIV). Data were collected approximately every six weeks between January 2016 and October 2017. We used a combination of thematic analysis and case study descriptions to explore gender identification among participants. Results Of the eight participants, only one accepted 'transgender' as a label, and even she used varying terms at different times to describe her identity. For participants, a feminine identity included dressing in normatively feminine clothes; using feminine terms, pronouns and names; and adopting stereotypically feminine mannerisms. Participants would switch between typically feminine and masculine norms in response to contextual cues and audience. For example, some participants accepted identification as masculine gay men amongst their family members. Among peers, they expressed their identity through typically more effeminate gender characteristics, for example self-identifying as "femgay". With partners they often also took on a feminine identity role, for example identifying as women in sexual and romantic relationships (meaning they viewed and expressed themselves as the feminine partner in the relationship). Conclusions Our findings are amongst the first exploratory and descriptive data of transfeminine people in South Africa. We show how transfeminine people navigate fluid gender identities that could pose a challenge for accessing and utilizing HIV services that are currently set up for transgender individuals or MSM. More work needs to be done to understand and respond to the diverse and shifting ways people experience their gender identities in this high HIV burden context.